Urban Art Infusion: Pengaruh Estetika Terhadap Evaluasi Produk Dan Niat Membeli - Adhitya, Reza; Sobari, Nurdin (Fakultas Ekonomi Universitas Gresik, 2023)
In light of the pandemic, there has been a shift in consumer behavior towards online services, particularly food delivery. It is crucial for business professionals to develop a strategy that helps them stand out, especially in the context of cloud kitchens. By incorporating artistic elements, particularly urban art, into the design of packaging, businesses have the potential to receive favorable evaluations from consumers and increase their intention to make purchases. This research study applies the SOR framework, utilizing artwork type and the artist's name as a stimulus. It examines how consumers perceive the product's aesthetics and luxury, as well as their evaluation of the product and intention to make a purchase as responses. The results of experimental research using the SEM method prove the effect of art infusion, which is fully mediated by the perception of luxury and aesthetics simultaneously except for fine art. However, the use of the artist's name does not have a significant effect. The results of the experiment, conducted using the SEM method, confirm the impact of art infusion effect, which is fully mediated by perceptions of luxury and aesthetics. This study paves the way for future researchers to explore the role of urban art in the realm of commerce. While understanding consumer behavior can offer a competitive edge to businesses, the inclusion of art infusion can immediately generate financial value.